PENGARUH KOMITE AUDIT, DEWAN KOMISARIS INDEPENDEN, KEPEMILIKAN INSTITUSIONAL DAN UKURAN PERUSAHAAN TERHADAP KINERJA KEUANGAN (Studi Kasus pada Perusahaan Food and Beverage yang Terdaftar di BEI Tahun 2016-2020) - Wulan Suryandani (Journal of Global Business and Management Review, 2022)
This study aims to explain the influence of the audit committee, independent board of commissioners, institutional ownership and company size on the financial performance of food and beverage companies listed on the Indonesia Stock Exchange in 2016-2020. The population used is all food and beverage companies listed on the IDX in 2016-2020. The data collection technique in the research was carried out using the documentation method with the sampling method, namely the purposive sampling method, in order to produce samples in accordance with the research criteria. The research sample was 13 companies with 65 observations. The data analysis technique used by the researcher was multiple linear regression analysis. The data was processed using the IBM SPSS 25 program. The results showed that partially the audit committee had an insignificant positive effect on financial performance, the independent board of commissioners had a significant positive effect on financial performance, institutional ownership had an insignificant positive effect on financial performance and firm size had a significant positive effect. on financial performance. The results of the determination test show the adjusted R2 value of 0.276, meaning that the financial performance variable can be explained by the four independent variables of the audit committee, independent board of commissioners, institutional ownership and company size of 27.6%, while the remaining 72.4% in this study is explained by other factors. which is not included in the regression model.